2023
DOI: 10.3389/fgene.2022.1092121
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee populations of the USA display restrictions in their mtDNA haplotype diversity

Abstract: The genetic diversity of the USA honey bee (Apis mellifera L.) populations was examined through a molecular approach using two mitochondrial DNA (mtDNA) markers. A total of 1,063 samples were analyzed for the mtDNA intergenic region located between the cytochrome c oxidase I and II (COI-COII) and 401 samples were investigated for the NADH dehydrogenase 2 (ND2) coding gene. The samples represented 45 states, the District of Colombia and two territories of the USA. Nationwide, three maternal evolutionary lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 71 publications
(120 reference statements)
1
14
0
1
Order By: Relevance
“…High levels of genetic variability are not uncommon in reared honey bees elsewhere [42,50,51,53,55,56]. For instance, the vast majority of honey bee populations from the USA have been characterized by high levels of haplotype diversity, ranging from 0.236 to 0.763 [10]. Similarly, honey bee populations from Iraq indicated considerable genetic diversity, ranging from 0.39 to 0.47 based on COI and 16S rDNA genes, with an average value of 0.44 [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of genetic variability are not uncommon in reared honey bees elsewhere [42,50,51,53,55,56]. For instance, the vast majority of honey bee populations from the USA have been characterized by high levels of haplotype diversity, ranging from 0.236 to 0.763 [10]. Similarly, honey bee populations from Iraq indicated considerable genetic diversity, ranging from 0.39 to 0.47 based on COI and 16S rDNA genes, with an average value of 0.44 [57].…”
Section: Discussionmentioning
confidence: 99%
“…This intraspecific diversity presents a fascinating parameter for studying the evolutionary biology, ecological dynamics, and genetic bases of complex traits. At least 30 different subspecies of A. mellifera have been described [8,9], classified into seven evolutionary different lineages, in which East European (C), West European (M), African (A, L and U), and Western Asia (O and Y) honey bees are included [10,11]. These subspecies are also known as "geographic races" owing to distributions that correspond to different geographic areas [12].…”
Section: Introductionmentioning
confidence: 99%
“…Novel haplotypes were named according to the nomenclature proposed in. [22] The three most dominant haplotypes were A9-828-2-DZA (24 %) followed by A8d (14 %) and A8-828-2-DZA (12 %). Other haplotypes were recorded: A1-637-3-DZA and A2-637-3-DZA (7.14 %); A8f, A3-637-3-DZA, A3-637-3-DZA (4.8 %) ; A5-638-2-DZA, A7-638-3-DZA, A14-637-3-DZA, A6-828-2-DZA, A10-827-2-DZA, A11-828-3-DZA, A12-828-3-DZA, A13-828-2-DZA (2.4 %) (Table 1).…”
Section: Subspecies Identificationmentioning
confidence: 93%
“…The investigation successfully delineated three distinct maternal evolutionary lineages, namely lineage C originating from the northern Mediterranean, lineage M originating from the western Mediterranean, and lineage A originating from Africa. The study revealed that the subspecies A. m. ligustica and A. m. carnica, found in the United States, exhibit a notable reliance on two distinct haplotypes (C1 and C2j) belonging to the same lineage [34].…”
Section: Haplotype Diversity In Usa Honey Bee Populationsmentioning
confidence: 96%